Motivation to Learn English for Junior High School Students in Yogyakarta - Namira Prasetya Rizky Ramadhani; Rahmi Munfangati (Jurnal Educatio FKIP UNMA, 2023)
The aim of study was to analyze the level of motivation in junior high school students, especially in English lessons. This is because the average English test scores in junior high schools are still not stable above the KKM (minimum completeness criteria). This type of research is a quantitative descriptive. The method used in this study is a survey and data collection techniques using a questionnaire. The sample in this study was 335 students from 16 junior high schools in Yogyakarta City. The results of the research on the motivation to learn English for junior high school students in the city of Yogyakarta based on the intrinsic motivation of learning English for junior high school students in the city of Yogyakarta were in a "very low" position of 1.78% (1 student), "low" 6.26% (21 students), " sufficient” 16.41% (55 students), “high” 32.53% (109 students), “very high” 44.47% (149 students). extrinsic motivation to learn English for junior high school students in the City of Yogyakarta is in a position of "very low" 1.02% (1 student), "low" 15.22% (52 students), "enough" 17.21% (58 students), "high" 38.30% (129 students), "very high" 28.25% (95 students). The conclusion of this study is that the motivation of junior high school students in the city of Yogyakarta can be concluded as "enough". There is a need for further studies on how to increase motivation so that students have a willingness to learn English.